Syncytin-mediated open-ended membrane tubular connections facilitate the intercellular transfer of cargos including Cas9 protein - Congyan Zhang; Randy Schekman (eLife, 2023)
Much attention has been focused on the possibility that cytoplasmic proteins and RNA may be conveyed between cells in extracellular vesicles (EVs) and tunneling nanotube (TNT) structures. Here, we set up two quantitative delivery reporters to study cargo transfer between cells. We found that EVs are internalized by reporter cells but do not efficiently deliver functional Cas9 protein to the nucleus. In contrast, donor and acceptor cells co-cultured to permit cell contact resulted in a highly effective transfer. Among our tested donor and acceptor cell pairs, HEK293T and MDA-MB-231 recorded optimal intercellular transfer. Depolymerization of F-actin greatly decreased Cas9 transfer, whereas inhibitors of endocytosis or knockdown of genes implicated in this process had little effect on transfer. Imaging results suggest that intercellular transfer of cargos occurred through open-ended membrane tubular connections. In contrast, cultures consisting only of HEK293T cells form close-ended tubular connections ineffective in cargo transfer. Depletion of human endogenous fusogens, syncytins, especially syncytin-2 in MDA-MB-231 cells, significantly reduced Cas9 transfer. Full-length mouse syncytin, but not truncated mutants, rescued the effect of depletion of human syncytins on Cas9 transfer. Mouse syncytin overexpression in HEK293T cells partially facilitated Cas9 transfer among HEK293T cells. These findings suggest that syncytin may serve as the fusogen responsible for the formation of an open-ended connection between cells.